2018
DOI: 10.1111/nep.12970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of anxiety and depression in Chinese peritoneal dialysis patients: A single centre study

Abstract: Anxiety and depression were also common among Chinese PD patients. Those in HSG were more likely to develop PD peritonitis. These psychological symptoms deserved early detection. Further studies are needed to investigate whether intervention can improve the clinical outcome of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
4
12
2
Order By: Relevance
“…On the other hand, the prevalence of depression and cognitive impairment are considerably lower in our present study than previous ones. Notably, depressive symptoms are present in 27.5% patients in this study, but in over 50% of Chinese PD patients in previous reports [10,33]. Similarly, cognitive impairment is present in over 20% of patients receiving hemodialysis [9] as well as PD [10], but is less than 8% in the present study.…”
Section: Discussioncontrasting
confidence: 48%
“…On the other hand, the prevalence of depression and cognitive impairment are considerably lower in our present study than previous ones. Notably, depressive symptoms are present in 27.5% patients in this study, but in over 50% of Chinese PD patients in previous reports [10,33]. Similarly, cognitive impairment is present in over 20% of patients receiving hemodialysis [9] as well as PD [10], but is less than 8% in the present study.…”
Section: Discussioncontrasting
confidence: 48%
“…The prevalence of depression in our study was 58.8%. The result is comparable to another local study, which reported 55% prevalence of depression among Chinese PD patients [4]. On the other hand, the worldwide prevalence of depression among dialysis population is reported to be 20-30% [27].…”
Section: Discussionsupporting
confidence: 82%
“…Depressed PD patients usually suffer from multiple physical and psychological symptoms, all of which affect their physical function, quality of life, and impede on their adherence to dialysis regimen [3]. A study in Hong Kong showed that 55% of PD patients were classified as having high emotional distress, which was an independent risk factor for the development of peritonitis [4]. Another metaanalysis also showed that the presence of depressive symptoms was a significant predictor of mortality in dialysis patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies reported that depression in patients with end stage renal disease is signi cantly associated with adverse medical outcomes, including the number of hospitalization [31] and cumulative hospital days [32], these studies were based on hemodialysis patients and may not be applicable to our patients. A local study showed that depression is signi cantly associated with mortality rate in Chinese peritoneal dialysis patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…Depressed PD patients usually suffer from multiple physical and psychological symptoms, all of which affect their physical function, quality of life, and impede on their adherence to dialysis regimen [3]. A study in Hong Kong showed that 55% of PD patients were classi ed as having high emotional distress, which was an independent risk factor for the development of peritonitis [4]. Another meta-analysis also showed that the presence of depressive symptoms was a signi cant predictor of mortality in dialysis patients [5].…”
Section: Introductionmentioning
confidence: 99%